Factors influencing satisfaction of non-medical healthcare personnel - Špačková, Iva; Holá, Jana (University of Pardubice, 2017)
Introduction: At present, monitoring of employee satisfaction is one of the standards of quality management in accredited hospitals. Assessment of satisfaction and finding incentives for greater engagement of employees should be a standard tool of personnel management. In healthcare organizations it is necessary to monitor employee satisfaction not only to ensure greater engagement, but also to prevent burnout syndrome, which also strongly affects the quality of provided health care. Aim: The aim of this paper is to present part of the results of a satisfaction survey, focusing on the significance of factors influencing satisfaction of non-medical healthcare personnel in an acute care hospital. Method: The data were collected in a satisfaction survey in an acute care hospital. The survey used anonymous online questionnaires, which were constructed on the basis of standardized questionnaires of the Gallup agency, surveys implemented in the project TNS AISA (Engagement of employees in the Czech Republic) and specific requirements of the hospital quality manager. Results: 1 178 non-medical healthcare employees included in the research sample mention as the most important factors influencing their perception of the social climate the following: good cooperation in the department, friendly interpersonal relationships and good relations with the immediate supervisor. Conclusion: The survey results lead to recommendations aimed particularly at improvement of internal communication and personnel management, which contribute to the creation of the desired social climate and organization culture. To stabilize the employees and improve their relationship with the organization it is necessary to build greater confidence in the top-level management through more transparent communication, focusing on the common goals and vision of the organization.
Keywords: engagement; non-medical healthcare personnel; organizational culture; professional satisfaction; social climate